Functional Evaluation of Physical Performance, Gait, Balance and Activities of Daily Living in Older Individuals With Long Covid Syndrome - Kosel, Izzettin; Aydin, Gamze; Tascilar Uyanik, Lacin Naz; Taşcilar Uyanik, Laçin Naz (Wiley, 2024)
Objective: The aim of our study was to evaluate the physical performance, balance, gait and activities of daily living (ADL) of older individuals with long COVID syndrome (LCS). Methods: A total of 124 individuals (49% women) with a mean age of 71.8 +/- 5.8 years were included in the study. Participants were divided into two groups, older individuals with LCS in the LCS group and older individuals who were not diagnosed with COVID-19 in the CON (control) group. Physical performance of participants was evaluated with the Alusti Test, balance and gait assessment was evaluated with the Tinetti Balance and Gait Assessment (TBGA), and ADL were evaluated with the Barthel Index (BI). Results: In the evaluations between groups, the mean score of active muscular mobility of right and left upper extremities, transfer supine position to sitting, trunk in sitting position and standing, which are among the subparameters of the Alusti Test, were statistically significantly lower in LCS compared to CON (p < .05). TBGA total score and gait section mean score of TBGA were statistically significantly lower in LCS than in CON (p < .05). There was no significant difference between the groups in the balance section of the TBGA and the mean BI scores (p > .05). Conclusions: It was concluded that physical performance parameters related to active muscular mobility of the upper extremity, transfer supine position to sitting, trunk in sitting position and walking in LCS were negatively affected by the disease, but this did not affect the level of balance and independence in ADL.
AYDIN, GAMZE/0000-0002-4952-2825
Keywords: Activities Of Daily Living; Gait; Geriatric Assessment; Long Covid; Postural Balance